Introduction of amino groups into acid-resistant MOFs for enhanced U(vi) sorption. Issue 2 (19th November 2014) - Bai, Zhi-Qiang; Yuan, Li-Yong; Zhu, Lin; Liu, Zhi-Rong; Chu, Sheng-Qi; Zheng, Li-Rong; Zhang, Jing; Chai, Zhi-Fang; Shi, Wei-Qun
Abstract : Amine grafting on MOFs greatly enhances the adsorbability of Cr-MIL-101 towards U(vi ) from an aqueous solution, and the enhancement depends on the coverage and flexibility of the grafted amino group. Abstract : Metal–organic frameworks (MOFs) have recently been receiving increasing attention in various scientific fields, including nuclear industry, due to their unique properties. In this work, the acid-resistant chromium-based MOF, MIL-101, and its amino derivatives were prepared to explore their potential usage in separation, removal and/or recovery of radionuclides from aqueous solutions. The synthesized MIL-101-NH2, MIL-101-ED (ED = Ethanediamine), and MIL-101-DETA (DETA = Diethylenetriamine) were characterized by X-ray diffraction spectrometry (XRD), infrared spectrometry (IR), N2 adsorption–desorption measurements, scanning electron microscopy (SEM) and thermogravimetric analysis (TGA), which confirm the successful modification of amino groups and the preservation of porous structures. The sorption performances of these materials toward U(vi ) from an aqueous solution were investigated in detail. It was found that all the amine-grafted MOFs were highly efficient in capturing U(vi ) compared to raw MIL-101. The sorption capacity of these MOFs for U(vi ) sorption follows the order of MIL-101-DETA > MIL-101-ED > MIL-101-NH2 > MIL-101, in which MIL-101-DETA possesses the highest sorption capacity of 350 mg g −1 at pH ∼5.5. Moreover, the sorbed U(vi ) can be easily desorbed by lowering the pH (pH ≤ 3.0), and the prepared materials also display a desirable selectivity toward U(vi ) in a solution containing a range of competing ions. Based on the FTIR and EXAFS characterizations, the sorption mode of U(vi ) onto MOFs is fully discussed. This work promises to provide a facile approach for developing acid-resistant MOFs toward a highly efficient and selective extraction of radionuclides from aqueous solutions.